2009
DOI: 10.2527/jas.2009-1850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter stocker growth rate and finishing system on: III. Tissue proximate, fatty acid, vitamin, and cholesterol content1

Abstract: Angus-cross steers (n = 198; 270 kg of BW; 8 mo) were used in a 3-yr study to assess the effects of winter stocker growth rate and finishing system on LM proximate, fatty acid, cholesterol, vitamin, and mineral composition. During the winter months (December to April), steers were randomly allotted to 3 stocker growth rates: low (0.23 kg/d), medium (0.45 kg/d), or high (0.68 kg/d). At the completion of the stockering phase, steers were allotted randomly within each stocker growth rate to a high concentrate (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
5
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 45 publications
(66 reference statements)
6
70
5
4
Order By: Relevance
“…Although the time on feed in the preexperimental phase could have affected the results of the experiment, previous studies indicated that feeding during the background phase marginally affected the quality of beef. Moreover, Duckett et al (2009) found no effect of the level of supplementation during the winter background on beef quality of pasture-or concentrate-finished steers. Similarly, Chicatún et al (2006) evaluated the beef quality of steers not supplemented or supplemented with two levels of corn silage during the growing phase and three levels of corn grain during the finishing phase, and the authors found no significant effect of the background feeding on the quality of beef.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 99%
“…Although the time on feed in the preexperimental phase could have affected the results of the experiment, previous studies indicated that feeding during the background phase marginally affected the quality of beef. Moreover, Duckett et al (2009) found no effect of the level of supplementation during the winter background on beef quality of pasture-or concentrate-finished steers. Similarly, Chicatún et al (2006) evaluated the beef quality of steers not supplemented or supplemented with two levels of corn silage during the growing phase and three levels of corn grain during the finishing phase, and the authors found no significant effect of the background feeding on the quality of beef.…”
Section: Intramuscular Fatty Acid Compositionmentioning
confidence: 99%
“…More information has recently become available on fatty acid composition and mineral and vitamin concentrations in different muscles from various breeds and under different production systems (Faucitano et al, 2008;Leheska et al, 2008;Purchas and Zou, 2008;Warren et al, 2008;De la Fuente et al, 2009;Duckett et al, 2009;Daley et al, 2010;Schonfeldt et al, 2010;Pordomingo et al, 2012;Sexten et al, 2012;Yuksel et al, 2012); however, little information is available regarding other components in beef that have been reported to be related to human health. Because of their potential protective effects, these components are generally referred to as bioactive compounds, or health-promoting active ingredients (Muller et al, 2002;Wyss et al, 2007;Hipkiss, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Further research has focused on the impacts of forage finishing on altering fatty acid composition of beef products, specifically reducing SFA content, improving the omega-6 to omega-3 FA ratio, enhancing CLA content and increasing B-vitamins and antioxidants. Beef from cattle produced in forage-based systems have a lower overall fat content and greater omega-3 FA and CLA content compared to beef from cattle finished using grain-based diets [77,[83][84][85]. Moreover, vitamin E and β-carotene concentrations have been found to be greater in beef finished on pasture compared to traditional finishing programs [84].…”
Section: Quality Differences Of Beef Productsmentioning
confidence: 96%
“…Beef from cattle produced in forage-based systems have a lower overall fat content and greater omega-3 FA and CLA content compared to beef from cattle finished using grain-based diets [77,[83][84][85]. Moreover, vitamin E and β-carotene concentrations have been found to be greater in beef finished on pasture compared to traditional finishing programs [84]. However, it is important to note that while the concentrations of beneficial fatty acids are greater in forage-finished beef, the total fat content is lower, and therefore may impact the total amount (as mg/d) of beneficial fatty acids in whole cuts of beef.…”
Section: Quality Differences Of Beef Productsmentioning
confidence: 99%